Personal and physical factors affecting the decision of patients to opt for spinal surgery: A case-control study. (May 2020) - Lam, William Wing-Kuen; Loke, Alice Yuen; Wong, Chun-Kwan
Abstract: Study design: A retrospective case-control study. Objectives: To explore the personal and physical factors influencing the decision of patients to opt for spinal surgery. Methods: The medical records of patients who attended the Spine Nurse Clinic of a hospital in Hong Kong in the year 2017 were retrieved and reviewed. Comparisons were made of the physical symptoms, myelopathy, sensory deficits, and level of disability of patients who decided to undergo spinal surgery (case) and those who did not (control). Results: Among the 122 medical records that were reviewed, it was found that 102 (83.6%) patients decided to undergo spinal surgery (case) while 20 (16.4%) chose not to (control). The patients in the case group were more likely to be unemployed than those in the control group (67% vs. 35%, p  = 0.01), to have higher scores in primary pain (4.75 vs. 2.6, p  = 0.003), higher scores in radiated pain (4.4 vs. 2.55, p  = 0.021), a higher level of disability as reflected in a higher Oswestry Disability Index (ODI) score (41.6 vs. 30.9, p  = 0.021), and a lower Japanese Orthopedic Association (JOA) score (13.7 vs. 15.6, p  = 0.008). Point biserial correlation showed that exercise tolerance was associated with the decision to undergo the surgery. A multiple regression analysis of the factors predictive of the decision to opt for spinal surgery showed that these factors were: unemployment (OR = 5.42, 95% CI: 1.689–17.44, p  = 0.005); severe primary pain (OR = 3.83, 95% CI: 1.241–11.832, p  = 0.02); and the presence of radicular symptoms (OR = 5.372, 95% CI: 1.704–16.93, p  = 0.004). Conclusion: The results of this study showed that besides physical factors such as pain radiation and disability level, which influenced the decision of patients to take the surgical option, patients who were unemployed were also more likely to choose surgery. This indicates that patients were worried about the possible impact of surgery on their employment, or on their ability to continue to work. It is important that patients be given a clear picture of the expected outcomes of their surgery, and that the information needs of patients regarding the surgery be explored and addressed.